Operational performance and modeling of a fuel cell/battery hybrid electric scooter - Biyik, Hilal; Unal, Sencer; Kayaoglu, Murat (Pergamon-Elsevier Science Ltd, 2026)
In recent years, the growing demand for individual transportation and increasing environmental awareness have brought hybrid electric vehicles to the forefront. In this study, a simulation-based hybrid electric scooter is developed by integrating a 3 kW PEM fuel cell and a 50.4 V 19.2 Ah lithium-ion battery through a fully active bidirectional DC-DC converter and a rule-based energy management system under the WMTC driving cycle. The proposed design addresses the limitations of battery-only scooters, such as short range and long charging time, while enhancing overall energy efficiency. Simulation results demonstrate that the hybrid mode achieves a range of approximately 300 km, corresponding to a 354-357 % improvement over the battery-only mode. Additionally, the regenerative braking mechanism provides around 10 % energy recovery, further extending driving time and improving battery performance. Unlike existing prototypes and commercial models that typically offer 100-150 km range, the proposed design quantitatively demonstrates both the significant range extension and the measurable contribution of regenerative braking under realistic driving conditions. These results highlight the practicality and sustainability of the proposed architecture as a promising solution for future light electric vehicle applications.
Keywords: Hydrogen fuel cell; Fuel cell/battery hybrid powertrain; Range extension with hydrogen; Light electric vehicle